Structural analysis and design to prevent disproportionate collapse - Fu, Feng (CRC Press, Taylor & Francis Group, 2016)
This book features a detailed introduction to progressive collapse and the use of FE programs such as ABAQUS in modeling. Case studies based on various types of structures such as multi-story buildings, long-span space structures, and bridges demonstrate failure mechanisms and effective mitigation methods in practice.